THE ROLE OF RANDALL'S ESL-LAB IN ENHANCING STUDENT MOTIVATION IN ESL CLASSROOMS - Nafisa, Luthfiyya Rahma; Wahyuni, Reti (ELLITE ( Journal of Education, Linguistics, Literature and Language Teaching), 2024)
Motivation plays a critical role in second language acquisition, particularly in developing listening skills, which are often overlooked in traditional ESL classrooms. This study examines the role of Randall’s ESL-Lab, a digital learning platform, in enhancing student motivation and engagement in listening activities. Data were collected through structured interviews with five participants from the English Teaching Department at UIN Walisongo. The findings reveal that the platform’s interactive features, level-based exercises, and accessibility significantly improve students' listening skills and foster a proactive approach to independent learning. Participants reported increased motivation to engage with English both in and outside the classroom, highlighting the platform's ability to make learning enjoyable and flexible. This study underscores the importance of integrating digital tools like Randall’s ESL-Lab into ESL instruction to enhance student motivation and listening comprehension. Further research is recommended to explore the long-term impacts and broader applications of such digital tools in language learning.